Gas Vesicle-Assisted Ultrasound Imaging for Effective Anti-Tumour CAR-T Cell Immunotherapy Efficacy in Mice Model - Huang Y; Yin Z; Xu R; Zheng W; Zhang Q; Zhou M; Xu Z; He Y; Liu S; Liu H (International Journal of Nanomedicine)
Yizhen Huang,1,2,* Zhao Yin,3,* Renhao Xu,2,* Wenyi Zheng,2 Qing Zhang,3 Meijun Zhou,2 Zhili Xu,2 Yanni He,2,4 Shuang Liu,3,4 Hongmei Liu1,2,4 1The Second School of Clinical Medicine, Southern Medical University, Guangzhou, 510515, People’s Republic of China; 2Department of Ultrasound, Institute of Ultrasound in Musculoskeletal Sports Medicine, The Affiliated Guangdong Second Provincial General Hospital of Jinan University, Guangzhou, 510317, People’s Republic of China; 3Department of Hematology, The Affiliated Guangdong Second Provincial General Hospital of Jinan University, Guangzhou, 510317, People’s Republic of China; 4Guangdong Engineering Technology Research Center of Emergency Medicine, Guangzhou, 510317, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongmei Liu; Shuang Liu, Email liuhm@gd2h.org.cn; liush@gd2h.org.cnIntroduction: Real-time tracking of Chimeric Antigen Receptor (CAR) T cell trafficking provides crucial information regarding the targeted migration, infiltration, and persistence of CAR-T cells within the tumour microenvironment (TME). This information is invaluable for the timely adjustment of auxiliary treatment strategies in clinical settings.Methods: We designed a gas vesicles (GVs)-labeled CAR-T (GVs@CAR-T) complex using nanoscale GVs with excellent ultrasound reflectivity to label CAR-T cells for post-labelling ultrasound molecular imaging.Results: GVs@CAR-T complexes achieved stable ultrasound imaging for up to five days. In vitro and vivo experiments demonstrated that GVs labelling did not affect the anti-tumour function of CAR-T cells. In a subcutaneous tumour model, ultrasound molecular imaging was used to monitor the targeted migration of systemically infused GVs@CAR-T cells, which revealed a positive correlation between specific infiltration and therapeutic efficacy.Conclusion: This study presents an efficient method for in vivo tracking of CAR-T cells and offers new insights for predicting the efficacy of CAR-T cell immunotherapy.Keywords: cell tracking, CAR-T therapy, ultrasound imaging, nanobubbles